1989
DOI: 10.1139/v89-027
|View full text |Cite
|
Sign up to set email alerts
|

High temperature–pressure aqueous oxidations. IV. A kinetic study of the oxidation and enolization of cyclohexanone in the presence of catalytic metal ions

Abstract: . 67, 165 (1989).The aqueous high pressure-temperature oxidation of cyclohexanone was found to be strongly catalyzed by silver, iron(III), and copper ions but not by aluminum, cobalt, manganese@), or nickel ions. The reactivities of the catalytic ions were inhibited by the acidic oxidation products. Accordingly, initial reaction velocities were determined and used to correlate the kinetic data. A detailed kinetic study of copper ion catalysis has shown that in the presence of that ion the reaction was first or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The above-indicated results imply that -caprolactone is not formed via a freeradical mechanism but, instead, via the Baeyer-Villiger mechanism. Taylor and Weygandt (1974; see also Thomas and Taylor, 1989) have proposed two nonchain mechanisms for the high-pressure aqueous oxidation of cyclohexanone. By the introduction of two kinds of typical water-soluble inhibitors respectively, they found that there was no evidence of an induction period as was found in the free-radical mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…The above-indicated results imply that -caprolactone is not formed via a freeradical mechanism but, instead, via the Baeyer-Villiger mechanism. Taylor and Weygandt (1974; see also Thomas and Taylor, 1989) have proposed two nonchain mechanisms for the high-pressure aqueous oxidation of cyclohexanone. By the introduction of two kinds of typical water-soluble inhibitors respectively, they found that there was no evidence of an induction period as was found in the free-radical mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Many model compounds have been studied with this perspective in mind. We can quote the work of Day et al, Willms et al., Thomas et al, Rivas et al, Hao et al, Shende et al, and Krisner . Most of the compounds studied have a partial order of one with respect to the initial substrate and a variable order with respect to the oxidant.…”
Section: Introductionmentioning
confidence: 99%